A simple, efficient and selective process for recycling La (and Al) from fluid cracking catalysts using an environmentally friendly strategy - Sadeghi, S. Maryam (2021)
Spent fluid cracking catalyst (FCC) is an abundant waste material derived from oil refining processes and notably characterized by its content in rare earth metals, such as cerium (Ce) and lanthanum (La). In this work, it was our main aim to develop a simple but effective flowsheet, based on a single acid assisted leaching step followed by two consecutive precipitation steps, for recovering La with high purity from the FCCs. Firstly, three (conventional, ultrasound- and microwave-assisted) leaching strategies were tested using two acids (sulphuric acid, H2SO4, and hydrochloric acid, HCl). Microwave-assisted leaching was revealed to be the most efficient [(99.4 ± 0.9)% of La] and fastest leached (1 cycle of 90 s) strategy using a lower concentration of acid (1 M HCl) and low liquid-solid ratio (L/S = 5). Subsequently, a sequential selective alkaline and oxalate precipitation was capable of producing an aluminium hydroxide with 88.7% of purity by increasing the pH up to 6 and a highly pure (99.7%) salt of lanthanum oxalate (which can be calcinated into a reusable lanthanum oxide) using a reduced oxalate concentration. The proposed process is independent of the initial Al concentration present in the hydrochloric acid FCCs leachates and widely applicable (for [La] > 0.04 M, complete La precipitation can be achieved regardless of its initial concentration using a molar [oxalate]/[La] ratio of 2). Moreover, it is significantly simpler and faster than existing methods and minimizes the consumption of energy and reagents to a bare minimum, with accompanying cost reduction and environmental benefits.